Narratives on migration and political polarization: How the emphasis in narratives can drive us apart - Eugenio Levi; Michael Bayerlein; Gianluca Grimalda; Tommaso Reggiani (Masaryk University, Faculty of Economics and Administration, 2023)
Nowadays, immigration is a polarizing topic in politics. In this paper, we investigate how much this political polarization is driven by the depiction narratives made of immigrants vis-a-vis the natives. Furthermore, we look at whether polarization is rooted in private preferences over narratives or in how they are endorsed in public settings and social media. Our empirical strategy consists of a survey experiment in the 2021 German elections and a field experiment on Twitter in which we manipulate the "pinned tweets" of experimental users. To build our narratives, we manipulate either the policy position - hostile toward or accepting migration - or an emphasis on the out-group, on the in-group, or on economic reciprocity. We find that political polarization is driven both by the policy position and emphasis in narratives. On Twitter, the out-group emphasis drives supporters of different parties apart, and the corresponding hostile narrative becomes the only one going viral. In the survey, right-wing participants prefer the reciprocity emphasis more, but we still find evidence of more polarization when allowing the participants to go public.
Keywords: D72; D91; C93; 330; immigration; narratives; political polarization; economic reciprocity; experiments; Twitter